Vitamin D status in exclusively breast-fed infants and their mothers - C. R., Vignesh Kumaran; S., Sundari; Ramesh, Shanthi (International Journal of Contemporary Pediatrics, 2018)
Background: India, despite being a tropical country has widespread vitamin D deficiency across all age groups. Present study was conducted to estimate the prevalence of subclinical hypovitaminosis D in exclusively breastfed infants and their mothers and also to study the correlation between the Vitamin D levels of these infants and their mothers. Methods: This cross-sectional study was conducted in 37 exclusively breastfed infants aged 6 months and below and their mothers. Under strict aseptic precautions 2 ml of blood was taken from each infant and mother and serum levels of 25(OH) D levels were measured by the direct ELISA method. Statistical analysis was done by using chi-square test, one-way ANOVA f-test and student independent t-test. Results: In present study, authors found that 78.3% of the mothers were Vitamin D deficient and 21.7% of the mothers were Vitamin D insufficient. Among the infants, authors found that 91.9% of the infants were Vitamin D deficient and 8.1% of the infants were Vitamin D insufficient. The association between dietary pattern and socio-economic class and mean maternal vitamin D levels was found to be statistically significant (p <0.05). Conclusions: There is a high prevalence of hypovitaminosis D amongst exclusively breastfed infants and their mothers. Hence, public awareness needs to be created regarding the benefits of sunlight exposure. Vitamin D fortification of food products and routine Vitamin D supplementation program for antenatal and lactating mothers and their young infants may be able to address this emerging public health problem in our country.